An Analytical Study the Virtue Honesty Side in Buddhism of the Character Kuan Yu as Appear in the Literary Work, about Story Ramance of the Three Kingdoms (Samkok) - Tanuphan, Nathakamol (Academic MCU Buriram Journal, 2017)
The study aimed to 1) study life history of Guan Yu , the character in the Romance of the Three Kingdoms, 2) to investigate the moral virtues of Guan Yu, the character in the Romance of the Three Kingdoms, and 3) to analyze the moral virtues of The Guan Yu according the Buddist principle in application for the current daily life. Finding showed that: An analysis of Guan Yu’s moral virtue in daily application from an analytical study based on the interview, it was found that most people know Guan Yu from their inheritance of worship from ancestors and from additional information taken from movies, plays, and readings etc. Most people know Guan Yu from his moral virtue of honesty and uprightness. He was also famous for his truthfulness and gratitude according to Buddhist principle, Sacca (Truthfulness) in the Garavasadhamma or the principle of the householder. The interviewees applied the Guan Yu’s virtue of truthfulness in daily work, instructing family members to do works honestly without cheating and taking advantage of others. For officials, the virtue of patience can be applied to perform their duty with pride and dignity and patriotism as the basis of life. This research carried on “honesty” of Guan Yu in the three kingdoms literature that lots of Chinese prosed him as God of honesty, we can see that honesty was most important in work and life in all occupations. There should carry out on honesty for cultivate to officer, soldier, police and staff in all organizations throughout in educational system for books as cartoon series, tale or cinema etc. even that the king phumiphol speech on important of benefit of honesty as follows, that honesty on any interest must be based on wisdom and consciousness as a result, there must be sustainable with wisdom and consciousness when he who make sense on wisdom and consciousness these will find the admire, confidence, satisfy in doing good and these will be supported the honesty in sustainably forever.